Fecal Fusobacterium nucleatum harbored virulence gene fadA are associated with ulcerative colitis and clinical outcomes. (August 2021) - Li, Dong-Hao; Li, Zheng-Peng; Yan Zhang; Zhou, Guan-Zhou; Ren, Rong-Rong; Zhao, Hui-Jun; Zhang, Na-Na; Li, Jian-Feng; Peng, Li-Hua; Yang, Yun-Sheng
Abstract: Object: Fusobacterium nucleatum ( F.nucleatum ), a gram-negative, obligately anaerobe of oral commensal，has been regarded as culprit of periodontal diseases previously and is being unveiled as possible pathogen of gastrointestinal disorders. The key virulence factor of F. nucleatum is FadA adhesin for binding and invading of the host's epithelial cells. Here, we detected fecal F.nucleatum and virulence gene fadA in patients with ulcerative colitis(UC) and evaluated the clinical relevance with UC. Methods and subjects: A total of 310 subjects were enrolled including 100 patients with UC, 70 healthy controls (HC), 70 patients with irritable bowel syndrome subtype diarrhea(IBS-D), and 70 colorectal cancer patients(CRC). Stool samples of UC patients compared with healthy controls as well as IBS-D and CRC patients were collected for Polymerase Chain Reaction(PCR) detection of F.nucleatum (based on 16s rRNA) and virulence gene fadA . Results: The detection rate of 16s rRNA based PCR for F . nucleatum of UC patients(39/100, 39.00%) and CRC(26/70, 37.14%) patients are significantly higher than HC (12/70, 17.14%, P < 0.01) and IBS-D patients (14/70, 20.00%, P < 0.01). Moreover, 19 samples were detected fadA positive from 39  F . nucleatum positive samples of UC patients (19/39, 48.72%), which is significantly higher than HC(2/12, 16.66%, P < 0.05). There were 3 samples detected fadA positive from 14  F . nucleatum positive samples of IBS-D patients(3/14, 21.43%) and 13 out of 26(50.00%) of CRC patients, which were both no significant differences compared with UC patients(21.4% vs 48.72%, P > 0.05; 50.00% vs 48.72%, P > 0.05). For both F.nucleatum and fadA gene positive patients, there were no statistical significances between erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), white blood cells(WBC), and hemoglobin compared with negative patients(defined by either F.nucleatum or fadA negative, or both negative). However, it is worth noting that detection rate of F.nucleatum with virulence gene fadA in patients of severe ulcerative colitis was significantly higher than patients with mild and moderate colitis(28.89% vs 10.91%, P < 0.05). In addition, the fecal F. nucleatum and fadA gene positive patients were more likely to have pancolitis other than left-sided colitis(pancolitis/left-sided colitis: 26.92% vs 10.42%, P < 0.05). Conclusions: The presence of F.nucleatum and fadA gene increased in UC patients, especially in patients with severe colitis and pancolitis. Strains of F.nucleatum harbored virulence gene fadA are suggested to play a role in the pathogenesis of UC. Highlights: Fusobacterium nucleatum an oral commensal, may become a potential pathogen linked periodontal diseases and gastrointestinal disorders. Fecal F.nucleatum of UC and CRC patients are more abundant than healthy controls and IBS-D patients. F.nucleatum possesses virulence gene fadA were more abundant in severe and pancolitis UC patients.